The The Effectiveness of Brainstorming and Mind Mapping to Teach Writing Narrative Text for Students with Extrovert and Introvert Personalities - Yuliani, Widya; Anggani Linggar Bharati, Dwi; Warsono, Warsono (English Education Journal, 2019)
Teaching English in SMA is teaching and learning a foreign language as a part of national education. Moreover, modern teaching technique should be developed to encompass the reality. This study aimed to measuring the effectiveness of brainstorming and mind mapping to teach writing narrative text with extrovert and introvert personalities. This research used 2x2 factorial experimental designs. The subjects were the students of class XI IPA 1 and XI IPA 2 of SMAN 2 Tegal. It was divided into two groups, they were extrovert and introvert personality. The instruments were used test, questionnaire, pre-test, and post-test. The finding of this research indicates that brainstorming technique was more effective than mind mapping technique to students with extrovert personality. While there was no significant difference between a student who was taught by using brainstorming technique and those taught by using mind mapping technique with introvert personality. It means that brainstorming technique is more effective to the students with extrovert personality, while mind mapping technique is effective to the students with introvert personality. Based on our findings, we conclude that both brainstorming technique and mind mapping technique can help and improve the students in writing skill for both students with extrovert and introvert personality.